Teenagers and Adolescents with Hemophilia-Need for a Specific Approach - Königs, Christoph; Motwani, Jayashree; Jiménez-Yuste, Víctor; Blatný, Jan; Factor Think Tank (Journal of clinical medicine, 2024)
Adolescents with hemophilia are a patient population with special requirements, having to manage their condition alongside the typical challenges of adolescence. Given the psychosocial impact of hemophilia and a desire to fit in with non-hemophilic peers, they may perceive treatment as more of a burden than a benefit. This can result in low adherence and a high risk of hemophilia-related complications. Hemophilia management has changed over time. To best inform shared decision-making with adolescent patients and their families, healthcare professionals must consider all the currently available evidence, highlighting treatment benefits as appropriate. They should also appreciate the requirements of all adolescents affected by hemophilia, including individuals with non-severe disease and girls/women. We discuss specific issues relating to the management of adolescents with hemophilia: prevention and management of bleeds, treatment adherence, joint health and physical activity, and other health-related issues. A multidisciplinary approach is advocated, and the potential role of digital technology in helping to equip patients with self-management skills to fully engage with treatment is considered. Currently, available hemophilia management generally enables adolescents with hemophilia to lead normal lives, participating in physical activities while maintaining good joint health. However, more work is required to help address both actual and perceived limitations.
Keywords: adolescence; hemophilia; management; adolescent